Diversity in the Major Polysaccharide Antigen of Acinetobacter Baumannii Assessed by DNA Sequencing, and Development of a Molecular Serotyping Scheme - Hu D. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0070329